Patient and hospital factors predict use of coronary angiography in out-of-hospital cardiac arrest patients. (May 2019) - Hanuschak, Tasha A.; Peng, Yingwei; Day, Andrew; Morrison, Laurie J.; Zhan, Cathy C.; Brooks, Steven C.
Abstract: Aim: To describe the association between patient- and hospital-level factors and coronary angiography among patients who suffer out-of-hospital cardiac arrest (OHCA). Methods: A population-based retrospective cohort study using data from 28 hospitals in Southern Ontario between March 1, 2010 and December 31, 2014. We included consecutive adult patients with atraumatic, OHCA, who achieved return of spontaneous circulation, and were alive at least six hours after hospital arrival. Multilevel logistic regression was used to measure the relationship between patient- and hospital-level covariates and receipt of coronary angiography. Results: Among 2578 consecutive patients, the mean age was 67(±15), 69% were male, 49% had a shockable initial cardiac arrest rhythm and 84% were comatose at hospital admission. Overall, 33% of the study population received coronary angiography. This varied markedly by hospital of first assessment (13%–70%). Factors associated with receiving coronary angiography included ST-segment elevation (OR = 21.30, CI95 16.17–28.04), a shockable initial cardiac rhythm (OR = 5.00, CI95 3.70–6.75), bystander AED use (OR = 2.51, CI95 1.49–4.23), EMS-witnessed arrest (OR = 2.49, CI95 1.62–3.81), initial admission to a PCI center (OR = 2.94, CI95 1.66–5.21), age (OR = 1.04, CI95 1.02–1.07 for age <55, OR = 0.91, CI95 0.88−0.94 for age ≥55), and pre-hospital ROSC (OR = 1.59, CI95 1.06–2.39). Conclusion: We identified patient- and hospital-level factors that explain some of the variability in the use of coronary angiography for OHCA. Future work should determine which post arrest patients will benefit most from urgent coronary angiography and evaluate knowledge translation strategies to ensure consistent delivery of best practices.